Polyphenol Conjugates by Immobilized Laccase: The Green Synthesis of Dextran‐Catechin. Issue 13 (6th May 2016) - Vittorio, Orazio; Cojoc, Monica; Curcio, Manuela; Spizzirri, Umile Gianfranco; Hampel, Silke; Nicoletta, Fiore Pasquale; Iemma, Francesca; Dubrovska, Anna; Kavallaris, Maria; Cirillo, Giuseppe
Abstract : Dextran‐catechin conjugate with high functionalization degree is synthesized by using a fully green process based on the chemistry of laccase immobilized on hydrogel film. By UV‐induced radical polymerization, the enzyme is immobilized into acrylate hydrogel film resulting in a highly performing biocatalyst (residual catalytic activity of 60% upon immobilization). 1 H‐NMR studies of dextran‐catechin conjugate allow the elucidation of the reaction mechanism and the assessment of the functionalization degree (128 mg of catechin per gram of conjugate). Cell viability studies performed in neuroblastoma cells clearly prove the anticancer potential of the conjugate (IC50 value of 17.03 μg mL −1 ) while being well tolerated by nonmalignant cells. The efficiency of this conjugate is found to be similar to dextran‐catechin, previously prepared by free radical reaction. This novel green approach of synthesis for dextran‐catechin opens new perspectives for the environmentally sustainable development of novel natural derived drugs to treat neuroblastoma and other cancers. Abstract : This paper explores the possibility to use immobilized Laccase as a biocatalyst for the preparation of a highly effective anticancer conjugate. Catechin and Dextran are linked with high yield in a full green context, and the resulting bioconjugate shows enhanced anticancer activity in neuroblastoma and no trace of toxicity on healthy cells.